THE IMPORTANCE OF INTRODUCING PUBLIC PRIVATE PARTNERSHIP MECHANISMS TO ENHANCE THE POTENTIAL OF PILGRIMAGE TOURISM - Uzakov Jamshid , Norboevich (THE INNOVATION ECONOMY, 2025)
This article provides a scientific justification of the role of public-private partnership (PPP) mechanisms in the development of pilgrimage tourism in Uzbekistan. It analyzes the economic, social, and cultural potential of the sector, as well as key challenges related to infrastructure, service quality, safety, and governance. Drawing on international experiences (Saudi Arabia, Turkey) and national practices, the article demonstrates the benefits of the PPP model as a tool for sustainable development. It also offers policy suggestions on digitalization, research-based approaches, and the creation of special pilgrimage tourism zones.